Challenges and Opportunities in Edge Computing - Varghese, B.; Wang, N.; Barbhuiya, Salim; Kilpatrick, P.; Nikolopoulos, D. (2016)
© 2016 IEEE. Many cloud-based applications employ a data centers as a central server to process data that is generated by edge devices, such as smartphones, tablets and wearables. This model places ever increasing demands on communication and computational infrastructure with inevitable adverse effect on Quality-of-Service and Experience. The concept of Edge Computing is predicated on moving some of this computational load towards the edge of the network to harness computational capabilities that are currently untapped in edge nodes, such as base stations, routers and switches. This position paper considers the challenges and opportunities that arise out of this new direction in the computing landscape.